The Law Of Exchanging Pulsa Into Money Using The Ibn Hazm Factors For Judges To Consider In Deciding To Cancel A Marriage In The Medan Religious Courts 2018-2022 - Rahmad Fauzi; Muhammad Amar Adly; Heri Firmansyah (UNIVERSITAS PAKUAN, 2023)
Fasakh or annulment of marriage is one way to cancel a marriage if the marriage is found to have inconsistencies in terms and conditions, fraud and deception. Fasakh or marriage annulment is actually carried out by the Religious Courts to fulfill the elements of state justice. Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law itself has the same views as the views of the Syafi'i School so that it has the same factors regarding the annulment of the marriage. This research uses a type of normative research with a statutory approach, a case approach and a comparative approach. The research results show that the author found two main factors that caused judges to cancel marriages at the Medan Religious Court in 2018-2022. Firstly because of the falsification of data and secondly the factor of falsification of circumstances (having been pregnant before the contract with another person. Therefore, the judge's considerations are in accordance with Law Number 1 of 1974 concerning Marriage, the Compilation of Islamic Law and the Syafi'i School of thought. So far the two things above This is a weakness in the administration of marriages. So many marriage annulment cases are found in the city of Medan. Therefore, there is a need to strengthen the legal administration of marriages. Indonesia should construct an independent layer of law, namely the Marriage Administration Law.